Public perceptions of energy choices: the influence of beliefs about climate change and the environment - Spence, Alexa; Poortinga, Wouter; Pidgeon, Nick; Lorenzoni, Irene (Multi-Science Publishing, 2010)
Past research has documented high levels of public concern for risks relating to nuclear power, with opposition to nuclear energy particularly being linked with general environmental concern. However recent UK energy policy, and other debates worldwide, has led to a repositioning of nuclear power as a ‘low carbon’ electricity source with potential benefits for mitigating climate change. Whilst many previous studies have examined perceptions of climate change and nuclear energy separately, this large British public attitude survey explores relationships between the two as well as with perceptions of other energy sources. Both general environmental concern and concerns about climate change were linked with positive evaluations of renewables and negative evaluations of nuclear power. We conclude that, despite the policy positioning of nuclear power as a low carbon electricity source, most people concerned about climate change continue to perceive nuclear negatively, something partially explained by general environmental concerns.